Sur-/interfacial regulation in all-solid-state rechargeable Li-ion batteries based on inorganic solid-state electrolytes: advances and perspectives. Issue 5 (4th March 2019) - Liang, Longwei; Sun, Xuan; Zhang, Jinyang; Sun, Jinfeng; Hou, Linrui; Liu, Yang; Yuan, Changzhou
Abstract : Advances in sur-/interfacial regulation in all-solid-state rechargeable Li-ion batteries based on inorganic solid-state electrolytes are reviewed and promising perspectives are proposed. Abstract : Recently, all-solid-state lithium-ion batteries (ASLBs) with stable inorganic solid-state electrolytes (ISEs) have been considered the most promising strategy to address the safety and energy density concerns of conventional lithium-ion batteries. The crucial challenge in exploring advanced ISEs lies in how to effectively overcome the charge-transfer resistance barrier originating from the solid–solid sur-/interfaces. In this review, up-to-date achievements in ISE-based ASLBs are summarized with a major focus on regulating sur-/interfacial behavior. Firstly, the current status, key findings, fundamental properties and ion-transport mechanisms of ISEs are presented and discussed in detail. Corresponding innovative methodologies to improve the ionic conductivity of ISEs are introduced. Then, structural/compositional characteristics and chemical/electrochemical behaviors occurring at solid–solid sur-/interfaces are systematically discussed. Practical strategies to address these sur-/interfacial issues, including regulation in humid air, cathode (anode)/ISEs, and grain boundaries are highlighted. Finally, comprehensive suggestions for an in-depth understanding and manipulation of the sur-/interfaces, and a meaningful perspective on future research directions in ISE-based ASLBs are provided. The present review gives constructive insights into solid–solid sur-/interfacial phenomena in the smart design of ISEs for advanced ASLBs, and will make research more efficient and provide fundamental understandings to allow for tremendous advances in ASLBs in the future.